A multiphase ISPH method for simulation of droplet coalescence and electro-coalescence. (August 2018) - Rahmat, A.; Yildiz, M.
Highlights: A new multiphase Incompressible Smoothed Particle Hydrodynamics (ISPH) method is developed for simulation of coalescence. The film drainage model is used to drain out particles of the surrounding fluid from the region between the droplets' interfaces. The head-on and head-off coalescence, and electro-coalescence of suspended droplets are simulated with the proposed method. Abstract: In this paper, a numerical algorithm is introduced for simulation of droplet coalescence and electro-coalescence within the framework of the Smoothed Particle Hydrodynamics (SPH) method. The algorithm is developed based on the film drainage model which is used for simulation of coalescence in mesh-dependent methods. The film drainage model allows the SPH particles which are entrapped between two colliding droplets to be discharged. The algorithm is validated with available numerical and experimental results. Then, the algorithm is employed to model two-dimensional coalescence problems for wide ranges of Weber number (0 < We < 30) and impact parameter (0 < β < 0.8). Moreover, the method is extended for the simulation of the electro-coalescence of 2D stationary droplets. Employing the leaky dielectric model, it is observed that both prolate and oblate deformed pair of droplets approach each-other, leading to the permanent coalescence.